Distribuição e probabilidade de ocorrência de precipitação na cidade de Pau dos Ferros/RN - Miranda, Victor Vinícius Rêgo (Universidade Federal Rural do Semi-Árido, 2018)
Precipitation is a meteorological element and predicting its probability of occurrence is of paramount importance for the Brazilian Northeastern semi-arid region. This work presents the annual and monthly variation of the precipitation during the years 1988 to 2017 of the city of Pau dos Ferros / RN, totaling 30 years. And these data were made available by the Agricultural Research Company of Rio Grande do Norte (EMPARN). Thus, the precipitations were determined for different levels of probability of occurrence with the aid of the incomplete Gamma probabilistic model, using the Kolmogorov-Smirnov adhesion test to verify the adequacy of the Gamma distribution. It was possible to verify that in 2008 occurred the highest annual precipitation with 1,235.00 mm and the lowest of 212,60 mm occurred in 1993, in which the average annual precipitation was 671.12 mm. The period of months with greater precipitations is between January and May, presenting values superior to 80 mm. Regarding dry and rainy days, it was obtained, respectively, the average of 334.47 and 32 days, being it possible to highlight March and April as the wettest months.
Keywords: Distribuição gama incompleta; Volume precipitado; Teste de aderência; Incomplete gamma distribution; Adhesion test; Volume precipitate; ENGENHARIAS::ENGENHARIA CIVIL